2017
DOI: 10.1038/ncomms15776
|View full text |Cite
|
Sign up to set email alerts
|

IL-21-mediated reversal of NK cell exhaustion facilitates anti-tumour immunity in MHC class I-deficient tumours

Abstract: During cancer immunoediting, loss of major histocompatibility complex class I (MHC-I) in neoplasm contributes to the evasion of tumours from host immune system. Recent studies have demonstrated that most natural killer (NK) cells that are found in advanced cancers are defective, releasing the malignant MHC-I-deficient tumours from NK-cell-dependent immune control. Here, we show that a natural killer T (NKT)-cell-ligand-loaded tumour-antigen expressing antigen-presenting cell (APC)-based vaccine effectively era… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 51 publications
4
110
2
Order By: Relevance
“…Importantly, as seen for the extent of differentiation of NK cells from poor responders, PB-CD34 + cells of two donors that gave rise to NK cells without measurable cytotoxicity if generated only with cytokines yielded NK cells that efficiently killed K562 cells when stimulated with K562/41BBL/mb15/mb21 cells during differentiation and expansion. This differential activity of NK cells derived from the same donor HSCs may be attributed to the previously described ability of IL-21 to reverse exhaustion and restore antitumor activity of NK cells after long-term culture [14,53]. Furthermore, in addition to killing of K562 cells, we observed enhanced lysis of target cells of different solid tumor origins by NK cells generated with the help of K562/41BBL/mb15/mb21 feeder cells.…”
Section: Discussionsupporting
confidence: 58%
“…Importantly, as seen for the extent of differentiation of NK cells from poor responders, PB-CD34 + cells of two donors that gave rise to NK cells without measurable cytotoxicity if generated only with cytokines yielded NK cells that efficiently killed K562 cells when stimulated with K562/41BBL/mb15/mb21 cells during differentiation and expansion. This differential activity of NK cells derived from the same donor HSCs may be attributed to the previously described ability of IL-21 to reverse exhaustion and restore antitumor activity of NK cells after long-term culture [14,53]. Furthermore, in addition to killing of K562 cells, we observed enhanced lysis of target cells of different solid tumor origins by NK cells generated with the help of K562/41BBL/mb15/mb21 feeder cells.…”
Section: Discussionsupporting
confidence: 58%
“…IL-21 resulted in a lower level of PD-1 on tumor antigen-specific CD8 + T cells. IL-21 was reported to reverse the innate NK cell dysfunction in tumors (56). We wondered whether IL-21 could also affect the adaptive dysfunctional CD8 + T cells and tested antigen-specific T cell responses after IL-21 treatment using MC38-OVA.…”
Section: Resultsmentioning
confidence: 99%
“…Here, as well, blocking TIM-3 with antibodies increased NK cell cytotoxicity and cytokine secretion. Additional recent studies identified TIM-3 expression as a marker of NK cell dysfunction and disease severity in colorectal cancer, esophageal cancer, endometrial cancer, and bladder cancer (96,(98)(99)(100)(101). Interestingly, TIM-3 engagement was initially shown to increase the expression of IFN-γ by NK cells in response to galectin-9, the β-galactoside binding lectin (123).…”
Section: Tim-3mentioning
confidence: 99%